2012
DOI: 10.1128/iai.06232-11
|View full text |Cite
|
Sign up to set email alerts
|

L-Ficolin and Capsular Polysaccharide-Specific IgG in Cord Serum Contribute Synergistically to Opsonophagocytic Killing of Serotype III and V Group B Streptococci

Abstract: ABSTRACTGroup B streptococci (GBS;Streptococcus agalactiae) are the most common cause of neonatal sepsis and meningitis. Serotype-specific IgG antibody is known to protect neonates against GBS infections by promoting opsonophagocytosis. The L-ficolin-mediated lectin pathway of the complement is also a potential mechanism for opsonization of GBS, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…Recent studies highlighted a role of the LP L-ficolin/ MASP complexes in the formation of the C4bC2a convertase on the GBS surface, initiation of C3b deposition, and phagocytic killing in the absence of specific Abs (36), a process that can be further amplified by anti-capule polysaccaride IgG and the AP convertase. The same authors suggested that deficiencies in L-ficolin in cord serum could be a risk factor for neonatal GBS infection (37). We concluded that, in absence of specific Abs, CIP could interfere with LP complement amplification.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies highlighted a role of the LP L-ficolin/ MASP complexes in the formation of the C4bC2a convertase on the GBS surface, initiation of C3b deposition, and phagocytic killing in the absence of specific Abs (36), a process that can be further amplified by anti-capule polysaccaride IgG and the AP convertase. The same authors suggested that deficiencies in L-ficolin in cord serum could be a risk factor for neonatal GBS infection (37). We concluded that, in absence of specific Abs, CIP could interfere with LP complement amplification.…”
Section: Discussionmentioning
confidence: 94%
“…There are now a number of studies that have confirmed that ficolin-A or its human homologue L-ficolin forms an integral part of the innate immune response to several bacteria and viruses (14)(15)(16)(17). Previous research has highlighted that L-ficolin opsonization of the bacterial species Salmonella enterica serovar Typhimurium (S. Typhimurium) and Streptococcus agalactiae (S. agalactiae) led to better phagocytosis and lectin complement pathway activation (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted that L-ficolin is able to function as an opsonin and enhance phagocytosis of S. Typhimurium and S. agalactiae (14,15). Due to the small size of the conidia, they can penetrate deep into the lungs, where they initially encounter the lung epithelium, in particular, type II pneumocytes (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ficolin-2 is known to bind many acetylated ligands (5) and various biological ligands, such as apoptotic cells (6), and may be important in renal transplantation (7) and preeclampsia (8). It also binds to several significant human pathogens, like group B streptococcus (9) and Salmonella enterica serovar Typhimurium (10), and to many Gram-positive bacterial teichoic acids (11). Thus, it may be important in host defense against these pathogens as well.…”
mentioning
confidence: 99%